The Two-pillar policy for the RMB - Urban J. Jermann; Bin Wei; Vivian Z. Yue (Federal Reserve Bank of Atlanta, 2019)
We document stylized facts about China's recent exchange rate policy for its currency, the renminbi (RMB). Our empirical findings suggest that a "two-pillar policy" is in place, aiming to balance RMB index stability and exchange rate flexibility. We then develop a tractable no-arbitrage model of the RMB under the two-pillar policy. Using derivatives data on the RMB and the U.S. dollar index, we estimate the model to assess financial markets' views about the fundamental exchange rate and sustainability of the policy. Our model is able to predict the modification of the two-pillar policy in May 2017, when a discretion-based "countercyclical factor" was introduced for the first time. We also examine the model's ability to forecast RMB movements.
Keywords: F31; G12; G13; G15; 330; exchange rate policy; two-pillar policy; managed float; Chinese currency; renminbi; RMB; central parity; RMB index